A Behavioral-Educational Intervention to Promote Pediatric Sleep During Hospitalization: A Pilot Randomized Controlled Trial. Issue 4 (4th July 2018) - Papaconstantinou, Efrosini A.; Hodnett, Ellen; Stremler, Robyn
ABSTRACT: Objective/Background: Hospitalization can contribute to common sleep difficulties in children. Interventions aimed at hospitalized children need to be developed and piloted with rigorous evaluative methods. The primary purpose of this study was to examine the feasibility and acceptability of a behavioral-educational intervention aimed at increasing nighttime sleep for hospitalized children. Participants: Hospitalized children aged 4–10 years and their caregivers. Methods: A pilot randomized, controlled trial with concealed-group allocation was conducted. Forty-eight hospitalized children (ages 4–10) and their care-givers were randomized to either the Relax to Sleep (RTS) intervention group ( n = 24) or the Usual Care (UC) comparison group ( n = 24). The RTS intervention was comprised of a one-on-one educational session for the parent that was guided by a standardized booklet containing information on sleep and instructions for training the child in the use of a diaphragmatic breathing exercise. UC participants received no information about sleep or relaxation. Children wore actigraphs for 3 days and nights and completed sleep diaries. Outcome measures included feasibility, acceptability, and sleep outcomes. Results: Parental reports indicated they enjoyed the discussion on sleep, found the information helpful, and their child found diaphragmatic breathing easy to use, and would use it again in the future. Children in the RTS group averaged 50 minutes more nighttime sleep, and had less wake after sleep onset time compared to children in the UC group. Conclusion: Sleep is critically important to children's health and well-being and should be given important consideration during hospitalization. Although the results of this pilot trial seem promising, more interventional studies are needed.